Construction and evaluation of a model of natural human motion based on motion diversity - Minato, Takashi; Ishiguro, Hiroshi (2008 3rd ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2008)
A natural human-robot communication is supported by a person's interpersonal behavior for a robot. The condition to elicit interpersonal behavior is thought to be related to a mechanism to support natural communication. In the present study, we hypothesize that motion diversity produced independently of a subject's intention contributes to the human-like nature of the motions of an android that closely resembles a human being. In order to verify this hypothesis, we construct a model of motion diversity through the observation of human motion, specifically, a touching motion. Psychological experiments have shown that the presence of motion diversity in android motion influences the impression toward the android.